Mitigating Tourism Social Costs during a Pandemic: Evaluating Residents' Perceptions and Behavioral Intentions. (March 2022) - Li, ShiNa; Li, Hengyun; Song, Haiyan; Chen, Mengxin
During a pandemic, tourism can inflict negative social costs on communities in tourist destinations. This study examines factors affecting residents' responses to policies to mitigate the social costs of tourism during a pandemic. Two hypothetical scenarios are analyzed. Study 1 investigates framing effects on residents' attitudes toward the effectiveness of policy measures; study 2 explores the impact of mental accounting on residents' willingness to pay. Findings show that residents perceive policy measures as more effective if their positive outcomes of such measures are highlighted. Also, residents are more willing to fund social cost mitigation with unearned income, such as anti-pandemic bonds, than through their salaries. This article contributes to academic debate on the efficacy of public policies in combating pandemics and extends the literature on framing and mental accounting in tourism research. Policy implications of these findings are also discussed.